Perencanaan Pemanfaatan Media Pembelajaran Digital Dalam Meningkatkan Kompetensi Sosial Guru - Ratna Dewi; Rizki Normayunita; Suharyanto Soro; Dinny Mardiana (Civiliza Publishing, Indonesia., 2025)
The use of digital learning media is one of the important strategies in answering the challenges of educational transformation in the digital era, especially in improving the quality of teachers as a whole. In addition to contributing to strengthening pedagogic and professional competence, digital learning media also has great potential in developing teachers' social competence, especially in the aspects of communication, collaboration, and professional interaction. This study aims to analyze in depth the planning and management of the use of digital learning media in improving the social competence of teachers at SDN 2 Plered. This study uses a qualitative approach with a descriptive method. The analytical framework refers to Henry Fayol's management functions which include planning, organizing, directing, coordinating, and controlling (POCCC), and is analyzed using the Input–Process–Output–Outcome (IPO) model. The research subjects consist of school principals, teachers, school operators, and related parties involved in the implementation of digital learning. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies. Data analysis is carried out interactively through the stages of data reduction, data presentation, and conclusion drawn, with the validity of the data maintained through source triangulation and technical triangulation. The results of the study show that the planning for the use of digital learning media at SDN 2 Plered has been supported by school policies and the availability of digital infrastructure facilities. The organization of resources and briefings carried out by the principal encourage teachers to use digital media more actively and collaboratively. The use of digital learning media has been proven to contribute positively to improving teachers' social competence, especially in communication skills, cooperation between teachers, and professional interaction. However, the limitations of internet network infrastructure and the lack of optimal control and evaluation systems based on social competency indicators are still the main obstacles in the implementation of digital learning.